Analysis of BRCA1 and BRCA2 mutations in Brazilian breast cancer patients with positive family history - Dufloth, Rozany Mucha; Carvalho, Sílvia; Heinrich, Juliana Karina; Shinzato, Júlia Yoriko; Santos, César Cabello dos; Zeferino, Luiz Carlos; Schmitt, Fernando (São Paulo Medical Journal, 2005)
CONTEXT AND OBJECTIVE: BRCA1 and BRCA2 are the two principal hereditary breast cancer susceptibility genes, and the prevalence of their mutations among Brazilian women is unknown. The objective was to detect BRCA1 and BRCA2 mutations in Brazilian patients with breast cancer, so as to establish genetic profiles. DESIGN AND SETTING: Cross-sectional study, in Centro de Atenção Integral à Saúde da Mulher, Universidade Estadual de Campinas, Brazil, and Institute of Pathology and Molecular Immunology, University of Porto, Portugal. METHODS: Thirty-one breast cancer patients with positive family history (criteria from the Breast Cancer Linkage Consortium) were studied, and genomic DNA was extracted from peripheral blood. Single-strand conformation polymorphism was used for the analysis of exons 2, 3, 5, and 20 of BRCA1. Cases showing PCR products with abnormal bands were sequenced. Exon 11 of BRCA1 and exons 10 and 11 of BRCA2 were directly sequenced in both directions. RESULTS: Four mutations were detected: one in BRCA1 and three in BRCA2. The BRCA1 muta- tion is a frameshift located at codon 1756 of exon 20: 5382 ins C. Two BRCA2 mutations were nonsense mutations located at exon 11: S2219X and the other was an unclassified vari- ant located at exon 11: C1290Y. CONCLUSION: The BRCA1 or BRCA2 mutation prevalence found among women with breast cancer and such family history was 13% (4/31). Larger studies are needed to establish the significance of BRCA mutations among Brazilian women and the prevalence of specific mutations.